A concise protecting-group-free synthesis of cephalosporolides E and F1. Issue 52 (10th June 2015) - Chaudhari, Dipali A.; Kattanguru, Pullaiah; Fernandes, Rodney A.
<x xml:space="preserve">Abstract</x> A concise protecting-group-free synthesis of cephalosporolides E and F has been accomplished from l-mannonic-γ-lactone by one-pot conversion to γ-vinyl-β-hydroxy-γ-lactone, cross-metathesis and Wacker-type oxidative spiroketalization.